Effect of coal mining on soil nitrogen distribution in semi-arid mining area of western China - Yang, Dejun; Zhang, Yajun; Chen, Xiuqin (Journal of Environmental Engineering and Landscape Management, 2019)
Soil nitrogen is a key indicator of soil quality and plays a significant role for plant growth. Therefore, it is very important to study soil nitrogen distribution, especially in semi-arid area of western China. Fewer scholars paid attention to the effect on soil nitrogen due to coal mining in semi-arid mining areas of western China. In this paper, soil samples of different locations were tested in both the loess region and the aeolian sand region in the Daliuta mining area in Shaanxi Province. The impacts of mining subsidence on soil nitrogen were investigated. The soil nitrogen distributions between the loess region and the aeolian sand region were compared, and used the principal component analysis method to evaluate soil quality in semi-arid mining area. The results showed that the comprehensive score of soil quality in the loess region was as follows: the internal pulling stress zone (NLS) > the external pulling stress zone (WLS) > the compressive stress zone (YS) > the neutral zone (ZX). The content of soil total nitrogen in YS-zone was the lowest in the loess region. The loss of nitrogen increased with time in the mining area, in which the total nitrogen loss at the depth of 0−15 cm was 0.27 g/kg, and the alkaline nitrogen loss at the depth of 0−15 cm was 1.08 mg/kg. In the aeolian sand region, the comprehensive score of soil quality was as follows: WLS > FC (the non-mining zone) > ZX > NLS > YS. The amount of soil nitrogen content in the loess region was larger than that in the aeolian sand region. It was found that for the loess region, the relationship between total nitrogen and nitrate nitrogen showed a significant positive correlation. It was also a significant positive correlation between ammonium nitrogen and alkaline nitrogen. In the aeolian sand region, there was a significant positive correlation between total nitrogen and alkaline nitrogen. There was no significant correlation among other nitrogen forms.